Ekuivalensi Formal & Dinamis dalam Dua Terjemah Bahasa Inggris pada Lagu Fi Hagat Karya Nancy Ajram: Kesetaraan Formal dan Dinamis dalam Dua Terjemahan Bahasa Inggris Lagu “Fi Hagat” Karya Nancy Ajram - Rugayyah binti Alwi Muladawilah; Moh. Zawawi (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Arabic songs have recently gained popularity among Indonesian audiences. Nancy Ajram, a Lebanese artist, is one of the most well-known singers whose songs are widely appreciated. The translation of Arabic song lyrics into English involves complex decisions regarding linguistic fidelity, emotional resonance, and cultural adaptation. Purpose: This research aims to identify the translation techniques used in each version and to analyze their implications, thereby providing a deeper understanding of how meaning, emotion, and cultural nuance are conveyed in song lyrics. Method: A qualitative descriptive approach with textual analysis was employed. Data were drawn from 17 representative verses from the original Arabic lyrics and their English counterparts on genius.com and lyricstranslate.com. Results and Discussion: To maintain naturalness and emotional impact in English, dynamic equivalence predominates, with the total usage rate 69% of both translations. Meanwhile, formal equivalence is applied selectively, accounting for 31% of both translations to preserve structural fidelity in specific phrases. The key differences between the two translations involve lexical shifts, syntactic restructuring, and cultural adaptations that alter connotations while still maintaining the overarching themes. Conclusions and Implications: This study reveals a marked preference for dynamic over formal equivalence, prioritizing emotional depth and cultural nuance over syntactic fidelity. This confirms that translating lyrics of romantic distress necessitates an interlingual approach to preserve the source text’s affective impact. Although offering a novel comparative perspective, the research is limited by its single-song scope and the exclusion of musical dimensions and audience reception.